PENERAPAN IPTEK ALAT CETAK PAVING BLOK TIGA DIMENSI DAN WORKSHOP PELAPORAN KEUANGAN PADA KELOMPOK USAHA ‘KAMANG’ DI DESA MATUNGKAS KABUPATEN MINAHASA UTARA - Peginusa, Stefani Switly; Supit, Teve W. M.; Priyono, Priyono; Sari, Dian Puspita (Jurnal Abdi Insani, 2024)
This community service program for the application of science and technology to the community involved KAMANG business group partners in Matungkas Village, District. Dimembe District. North Minahasa with the main problem is in the production sector. To overcome this problem, empowerment activities were carried out and the application of three-dimensional block paving formwork technology was carried out. The aim is the application of science and technology to society through the creation of three-dimensional paving block printing formwork which is expected to increase the production of business groups. The methods used were technology workshops and Community Based Research and Participatory Action Research. Through this service activity, quality three-dimensional paving printing forms are obtained. Through training in financial report management skills, group members' ability to prepare financial reports increases but still requires coaching related to marketing management, especially with currently developing digital technology. For future product development, it is necessary to collaborate with educational institutions and other private parties to provide raw materials, product quality testing and a good marketing management system. In the end, with the PkM implemented, the Kamang business group can develop and open up job opportunities for the surrounding community.